The Influence of 1 on 1 Games on the Ball Dribbling Ability of Students at MTs Nurul Cholil 03 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical education plays an important role in improving students' motor skills and fitness. One important aspect of playing football is a dribbling technique, which requires good coordination, balance, and control. However, many students still have difficulty dribbling the ball properly. Therefore, this study aims to analyze the effect of one-on-one games on improving students' dribbling skills at MTs Nurul Cholil 03. The purpose of this study was to determine the effect of one-on-one games on dribbling skills in students at MTs Nurul Cholil 03. This study used a quantitative method with a pre-experimental experimental approach (pretest-posttest design). The sample used was 20 students from classes VII A and VIII A who had difficulty dribbling the ball. Data collection techniques were carried out through observation, documentation, and dribbling skills tests before and after treatment. Data were analyzed using the Shapiro-Wilk normality test and hypothesis testing with paired t-tests using SPSS 20 software. The results of the normality test showed that the pretest and posttest data were normally distributed. Hypothesis testing shows a significance value of 0.005